Smash-up : the story of a woman - Heisler, Stuart, 1894-1979; Hayward, Susan, 1917-1975; Universal Pictures Company; Cinetel Films ([North Hollywood, CA] : Universal Pictures Company, Inc., 1947)
Angie Evans, fast-rising nightclub singer, interrupts her career to marry struggling songwriter Ken Conway. When Ken lucks into a career as chart-topping radio crooner, Angie is forced into idle luxury which proves her downfall. Her potential alcoholism burgeons and Ken remains clueless concerning his responsibility for her problems. --
Susan Hayward, Lee Bowman, Marsha Hunt, Eddie Albert..
Cinematographer, Stanley Cortez; editor, Milton Carruth; music, Frank Skinner.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Singers -- Drama; Women singers -- Drama; Composers -- Drama; Man-woman relationships -- Drama; Alcoholism -- Drama; Feature films; Internet videos; Streaming video